INTEGRASI KEARIFAN LOKAL BAKAR UHA DI DESA LIANG DENGAN DESAIN PEMBELAJARAN MODEL PROBLEM SOLVING MATERI KALOR DAN PERPINDAHANNYA - Tamaela, E S; Limba, A; Sopacua, F; Manuhuttu, L; Radjaudu, D; Tehuayo, S (Universitas Pattimura, 2023)
Local wisdom is a characteristic or culture of a particular area that is preserved. Maluku province which consists of islands has a variety of local wisdom. These local wisdoms can be integrated with classroom learning. One form of local wisdom found in Liang Village, Central Maluku Regency is the making of Uha. Uha is a typical food of Liang Village. This food is made from sago and is maintained until now. The process of making Uha can be integrated with learning physics, especially the material of heat and its transfer. Because it can help students understand abstract concepts, teachers need to be equipped with knowledge of the process of developing devices with local local wisdom. The provisioning process involved all teachers at SMA Negeri 47 Central Maluku. At the writing of this article is only limited to physics learning tools. One that has been developed is a problem solving learning model with the local wisdom of Bakar Uha